Comparative Study of Real-Time Semantic Segmentation Networks in Aerial Images During Flooding Events - Farshad Safavi; Maryam Rahnemoonfar (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing, 2023)
Real-time semantic segmentation of aerial imagery is essential for unmanned ariel vehicle applications, including military surveillance, land characterization, and disaster damage assessments. Recent real-time semantic segmentation neural networks promise low computation and inference time, appropriate for resource-limited platforms, such as edge devices. However, these methods are mainly trained on human-centric view datasets, such as Cityscapes and CamVid, unsuitable for aerial applications. Furthermore, we do not know the feasibility of these models under adversarial settings, such as flooding events. To solve these problems, we train the most recent real-time semantic segmentation architectures on the FloodNet dataset containing annotated aerial images captured after hurricane Harvey. This article comprehensively studies several lightweight architectures, including encoder–decoder and two-pathway architectures, evaluating their performance on aerial imagery datasets. Moreover, we benchmark the efficiency and accuracy of different models on the FloodNet dataset to examine the practicability of these models during emergency response for aerial image segmentation. Some lightweight models attain more than 60% test mIoU on the FloodNet dataset and yield qualitative results on images. This article highlights the strengths and weaknesses of current segmentation models for aerial imagery, requiring low computation and inference time. Our experiment has direct applications during catastrophic events, such as flooding events.